2012
DOI: 10.1007/s10059-012-0080-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Arabidopsis Translationally Controlled Tumor Protein Gene AtTCTP Enhances Drought Tolerance with Rapid ABA-Induced Stomatal Closure

Abstract: Translationally controlled tumor protein (TCTP), also termed P23 in human, belongs to a family of calcium-and tubulin-binding proteins, and it is generally regarded as a growth-regulating protein. Recently, Arabidopsis TCTP (AtTCTP) has been reported to function as an important growth regulator in plants. On the other hand, plant TCTP has been suggested to be involved in abiotic stress signaling such as aluminum, salt, and water deficit by a number of microarray or proteomic analyses. In this study, the biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 52 publications
4
59
0
2
Order By: Relevance
“…TCTP from the rubber tree (Hevea brasiliensis) was found to be regulated by drought, low temperature, high salt, ethylene, hydrogen peroxide or wounding (Deng et al 2016;Li et al 2013). This is consistent with the observation that overexpression of TCTP in Arabidopsis resulted in increased drought tolerance of the plants (Kim et al 2012a). Moreover, in the cabbage (Brassica oleracea), TCTP was found to be involved in maintaining tolerance to heat, cold and to salt stresses (Cao et al 2010).…”
Section: Involvement In Cellular Stress Responsessupporting
confidence: 80%
See 1 more Smart Citation
“…TCTP from the rubber tree (Hevea brasiliensis) was found to be regulated by drought, low temperature, high salt, ethylene, hydrogen peroxide or wounding (Deng et al 2016;Li et al 2013). This is consistent with the observation that overexpression of TCTP in Arabidopsis resulted in increased drought tolerance of the plants (Kim et al 2012a). Moreover, in the cabbage (Brassica oleracea), TCTP was found to be involved in maintaining tolerance to heat, cold and to salt stresses (Cao et al 2010).…”
Section: Involvement In Cellular Stress Responsessupporting
confidence: 80%
“…In this function, the Arabidopsis and Drosophila proteins are exchangeable in their respective systems (Brioudes et al 2010). The microtubule-binding activity of AtTCTP has been investigated in yet another paper (Kim et al 2012a); the binding to actin filaments (Bazile et al 2009) and identification of an actin-binding site (Tsarova et al 2011) were also reported for TCTP.…”
Section: Tctp a Microtubule Stabilising Protein At The Mitotic And Tmentioning
confidence: 99%
“…12 More recently, a role in stomatal closure and thus response to water deficit has been shown for AtTCTP1. 13 Pumpkin TCTP has been isolated from phloem and found to interact with CmPP16 and suggested to be necessary for its phloem root-ward transport. 14 The isolation of a TCTP mRNA homolog from Lupinus phloem sap exudates indicates that this gene may also function in a non-cell autonomous fashion in plants as well.…”
Section: Introductionmentioning
confidence: 99%
“…These include wellestablished MAPs such as MAP65-1 and MAP65-2 (Smertenko et Mao et al, 2005), seven kinesins (two family 14) (Reddy and Day, 2001;Lee and Liu, 2004;Zhu and Dixit, 2012), AIR9 (Buschmann et al, 2006), and AIM1 (Chuong et al, 2002). Other candidate MAPs based on bibliographical cross-referencing (Supplemental Data Set 3) included MAP190/EMB1579 (Igarashi et al, 2000), seven dynamin-related proteins (Maeda et al, 1992;Hong et al, 2003;Hamada et al, 2006), PLD (Gardiner et al, 2001), CSI1 (Bringmann et al, 2012;Li et al, 2012;Mei et al, 2012), TCTP (Kim et al, 2012), and THO2 (Hamada et al, 2009). Proteins associated with the posttranslational modification of microtubules Color-coded heat map shows the hierarchical clustering of subsets of proteins with distinct accumulation profiles during TE differentiation, expressed as log 2 -fold ratio (relative to t 0 h).…”
Section: Proteomic Analysis Of Microtubule Interacting Proteins Durinmentioning
confidence: 99%